Vortex‐Wide Detection of Large Aspherical NAT Particles in the Arctic Winter 2011/12 Stratosphere. Issue 22 (16th November 2019) - Woiwode, W.; Höpfner, M.; Bi, L.; Khosrawi, F.; Santee, M. L.
Abstract: Micron‐sized HNO3 ‐containing particles in polar stratospheric clouds are known to denitrify the polar winter stratosphere and support chemical ozone loss. We show that populations of nitric acid trihydrate (NAT) particles with volume‐equivalent median radii of 3–7 μm can be detected vortex‐wide by means of infrared limb sounding. Key for detection are the applied optical characteristics of highly aspherical particles consisting of the β‐NAT phase. Spectroscopic signatures and ambient conditions of detected populations show that these particles play a key role in denitrification of the Arctic winter stratosphere. Complementary gas‐phase HNO3 observations indicate collocated highly efficient HNO3 sequestration within days and are consistent with measured spectral signals of populations of large NAT particles. High amounts of condensed gas‐phase equivalent HNO3 exceeding 10 ppbv and long persistence of detected populations, despite expected gravitational settling, imply that our understanding of the particles is incomplete. Plain Language Summary: In the past, micron‐sized HNO3 ‐containing particles characterized by significant gravitational settling and denitrifying the polar stratosphere were postulated to explain observed HNO3 ‐distributions in the polar stratosphere. The long‐sought large nitric acid trihydrate particles were observed for the first time about 20 years ago. However, important aspects of these particles remained unclear. A decade later, field observations of these particles were found to be not compatible with established model simulations and question our understanding of polar stratospheric chemistry. Here, we present a new method to detect such populations of HNO3 ‐containing particles by using infrared limb observations. Our study contributes redundant spectral and thermodynamic evidence for the particle composition and furthermore indications of particle shape. Based on complementary observations, we track populations of large nitric acid trihydrate particles during the Arctic winter 2011/12. We find rapid particle growth, highly efficient sequestration of gas‐phase HNO3, and at the same time unexpectedly long persistence times of the observed populations. All of these aspects are not captured by state‐of‐the‐art model simulations reported in the literature. Thus, our method provides the prerequisite to test and optimize model simulations of these particles during entire winters, with the goal to improve future projections of polar stratospheric ozone. Key Points: Populations of aspherical nitric acid trihydrate particles with median radii ≥3 μm can be detected vortex‐wide The populations grow fast and consume high amounts of gas‐phase HNO3 High amounts of condensed HNO3 and long persistence of detected populations are inconsistent with model simulations